Budaya Nongkrong, Ruang Sosial, dan Pembentukan Identitas Mahasiswa TV Film Angkatan 2024 di ISI Padang Panjang - Aysah Zakia Utami; Suci Rahmadhani; Basyarul Aziz (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Hanging out culture is a form of social activity that has developed among university students as part of the urban lifestyle. In a university environment, hanging out activities not only serve as a way to fill free time but also serve as a social space that allows for interaction, information exchange, solidarity building, and the formation of group identity. This study aims to examine the hanging out culture among students in the Television and Film Study Program at the Indonesian Institute of the Arts (ISI) Padangpanjang, class of 2024, and to analyze the role of this activity in the process of student identity formation. The study used qualitative methods with a descriptive approach. Data collection was conducted through observation, interviews, and documentation of TV and Film students from the class of 2024 who actively hang out in the food court of the Faculty of Film and Digital Recording Arts (FFSRD) and the campus grounds. The data obtained were analyzed by identifying interaction patterns, habits, and shared experiences that emerge during these hangouts, then interpreted using Damsar's social space theory. The results indicate that hanging out culture has become an integral part of the social life of TV and Film students at ISI Padangpanjang. This activity not only serves as a means of recreation and release from boredom after lectures, but also serves as a medium for building social relationships, strengthening solidarity, exchanging academic information, and discussing various matters related to the world of film and audiovisual production. Repeated interactions in the hangout space generate a strong sense of togetherness and form a collective identity as "TV Film kids." This study shows that the FFSRD food court and the area around the field function as social spaces that play an important role in the process of student identity formation. Thus, the hangout culture not only has a social function but also contributes to the formation of group identity on campus.